2018
DOI: 10.1167/iovs.18-25301
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the Four-Layered Retinal Vasculature Using High-Resolution Optical Coherence Tomography Angiography Reveals the Microcirculation Unit

Abstract: Citation: Muraoka Y, Uji A, Ishikura M, Iida Y, Ooto S, Tsujikawa A. Segmentation of the four-layered retinal vasculature using high-resolution optical coherence tomography angiography reveals the microcirculation unit. Invest Ophthalmol Vis Sci. 2018;59:5847-5853. https://doi.org/ 10.1167/iovs.18-25301 PURPOSE. To differentiate the four layers of the retinal vessel network in the human macula and examine their morphologic features using high-resolution optical coherence tomography angiography (HR-OCTA).M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In recent studies, Balaratnasingam et al22 histologically showed the capillary-free zone (approximately 30–50 μm in diameter) along parafoveal retinal arteries and also demonstrated that four different OCTA devices could clearly visualize this zone along retinal arteries but not veins. Muraoka et al23 also demonstrated that averaged high-resolution OCTA images enhanced visualization of the capillary-free zones around the arteries. These findings suggest one means by which arteries can be directly identified on OCTA alone.…”
Section: Introductionmentioning
confidence: 98%
“…In recent studies, Balaratnasingam et al22 histologically showed the capillary-free zone (approximately 30–50 μm in diameter) along parafoveal retinal arteries and also demonstrated that four different OCTA devices could clearly visualize this zone along retinal arteries but not veins. Muraoka et al23 also demonstrated that averaged high-resolution OCTA images enhanced visualization of the capillary-free zones around the arteries. These findings suggest one means by which arteries can be directly identified on OCTA alone.…”
Section: Introductionmentioning
confidence: 98%
“…The recently developed high-resolution OCTA can segment additional vascular layers and visualize the pre-capillary arteriole, which is known to play an important role in retinal vascular function and autoregulation. 24 A further study using high-resolution OCTA could contribute to expanding our understanding of the pathophysiology in DR.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of OCTA, a number of models have been proposed regarding connections among the retinal vascular plexuses [29][30][31][32].…”
Section: Evaluation Of the Vascular Layers With Octamentioning
confidence: 99%
“…The small capillaries arise from SCP arterioles and drain into SCP venules. The GCL slab enhances visualization of the capillary-free zones around the arteries and arterioles and helps differentiate arterial and venous systems [32]. Using OCTA, SCP arterioles were demonstrated to be located more superficially than SCP venules [30].…”
Section: Evaluation Of the Vascular Layers With Octamentioning
confidence: 99%
See 1 more Smart Citation